2020
DOI: 10.1155/2020/8716927
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antiproliferative Potential of Bioactive Molecules Ursolic Acid and Thujone Isolated from Memecylon edule and Elaeagnus indica and Their Inhibitory Effect on Topoisomerase II by Molecular Docking Approach

Abstract: The present study aimed to evaluate the antioxidant and antiproliferative potential of ursolic acid and thujone isolated from leaves of Elaeagnus indica and Memecylon edule and their inhibitory effect on topoisomerase II using molecular docking study. The isolated ursolic acid and thujone were examined for different types of free radicals scavenging activity, the antiproliferative potential on U-937 and HT-60 cell lines by adopting standard methods. Further, these compounds were docked with the active site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 35 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…The latter are triterpenoids, a class of isoprenoid-based secondary metabolites. OA and UA were shown to possess antiinflammatory (Kashyap et al 2016), antitumoral (Pięt and Paduch 2018), hepatoprotective (Gutiérrez-Rebolledo et al 2016) and antioxidant (Srinivasan et al 2020;Guo et al 2020) properties among others. These properties make oleanolic and ursolic acid interesting candidates for clinical application, which could result in high future demand.…”
Section: Introductionmentioning
confidence: 99%
“…The latter are triterpenoids, a class of isoprenoid-based secondary metabolites. OA and UA were shown to possess antiinflammatory (Kashyap et al 2016), antitumoral (Pięt and Paduch 2018), hepatoprotective (Gutiérrez-Rebolledo et al 2016) and antioxidant (Srinivasan et al 2020;Guo et al 2020) properties among others. These properties make oleanolic and ursolic acid interesting candidates for clinical application, which could result in high future demand.…”
Section: Introductionmentioning
confidence: 99%
“…Salau et al [ 3 ] found that UA was more potent than ascorbic acid as reflected by IC 50 values obtained by DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging potential (2.08 μg/mL and 7.64 μg/mL, respectively) and ferric reducing antioxidant power (FRAP) (0.75 μg/mL and 20.17 μg/mL, respectively) assays. Although the difference may arise from the distinction of hydrophilicity and the selectivity of the assays [ 78 ], it strongly suggests the antioxidant potential of UA. Moreover, the pre-treatment with UA has abolished kainate-induced free radical generation in primary culture of hippocampal neurons [ 79 ].…”
Section: Neuroprotective Effects Of Ursolic and Oleanolic Acidsmentioning
confidence: 99%
“…Antioxidant effects of UA have been demonstrated in a wide range of experimental models (see Table 2 ), both in vitro and in vivo, with single or repeated administration. UA has been shown to increase the activity of CAT [ 80 , 81 , 82 ], SOD [ 3 , 77 , 79 , 81 ], glutathione (GSH) [ 3 , 80 , 81 , 82 ], GP [ 78 ] and to activate the Nrf2-pathway [ 83 , 84 ]. The final result of the majority of experiments was the reduction of lipid peroxidation expressed as the decrease in the level of malondialdehyde (MDA) [ 3 , 80 , 81 , 82 , 83 , 84 ].…”
Section: Neuroprotective Effects Of Ursolic and Oleanolic Acidsmentioning
confidence: 99%
“…Salau et al [3] found that UA was more potent than ascorbic acid as reflected by IC 50 values obtained by DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging potential (2.08 µg/mL and 7.64 µg/mL, respectively) and ferric reducing antioxidant power (FRAP) (0.75 µg/mL and 20.17 µg/mL, respectively) assays. Although the difference may arise from the distinction of hydrophilicity and the selectivity of the assays [78], it strongly suggests the antioxidant potential of UA. Moreover, the pre-treatment with UA has abolished kainate-induced free radical generation in primary culture of hippocampal neurons [79].…”
Section: Neuroprotective Effects Of Ursolic and Oleanolic Acids 41 Neuroprotective Effects Of Ursolic And Oleanolic Acids In Neurodegenermentioning
confidence: 99%